A comparative study of the outcomes of potent topical steroids versus topical tretinoin in patchy alopecia areata of scalp - Hussain, Asma Arif (International Journal of Research in Dermatology, 2019)
Background: Alopecia areata (AA) is a common condition causing patchy alopecia of scalp. It can follow an unpredictable course with spontaneous exacerbations and remissions. Various therapeutic options have been tried to alleviate the cosmetic concern of the patient. The objective of this study is to compare the efficacy and safety of potent topical steroid versus topical 0.05% tretinoin in limited patchy alopecia areata of scalp. Methods: In this study 50 patients of age group above 5 years and of both sexes having localized alopecia areata of scalp (<5 patches and <25% scalp involvement) were included in the study after taking an informed consent. It was a randomized prospective study done for a period of 12 weeks. Excluding the age and sex bias, patients were distributed into two treatment groups A and B. Group A was treated with 0.05% betamethasone dipropionate (BMD) cream applied twice daily. Group B was treated with topical 0.05% tretinoin cream applied twice daily. The response was assessed in every patient subjectively as well as objectively by alopecia grading scale and regrowth score (RGS) at the end of 12 weeks. Results: We found that 72% of patients in Group A showed statistically significant clinical improvement (RGS 3 and 4) when compared to 36% patients in Group B. Conclusions: It can be concluded that 0.05% BMD is still the most effective and economical topical treatment in less extensive forms of AA. However topical 0.05% tretinoin also gives a fairly good response. But further studies with tretinoin are needed to establish its role in limited alopecia areata.